Technical and economic aspects of furfural and ethanol co-production from sugarcane bagasse and harvest residues, annexed to a sugar mill - Ntimbani, Rhulani Nicolas (Stellenbosch : Stellenbosch University, 2021)
ENGLISH ABSTRACT: Lignocellulose biomass has potential to reduce the consumption of fossil resources. Furfural and ethanol are some of the most promising bioproducts that can be produced from lignocellulose biomass, with the potential to replace fossil-based products. Commercial furfural production is performed in a one-stage process, where furfural is recovered in the vapour phase leaving the reactor. Furfural may also be produced using a two-stage process, whereby lignocelluloses are fractionated into hemicellulose-rich hydrolysate and cellu-lignin solid residues, followed by conversion of the solubilised hemicelluloses into furfural in a subsequent process unit. Conditions of the one-stage furfural process reduce biomass recalcitrance but tend to degrade cellulose components and produce yeast inhibitors. In contrast, conditions in the two-stage furfural process minimise cellulose degradation, while increasing enzymatic susceptibility of residual biomass. Most studies that consider ethanol production from the cellu-lignin residues from the one-stage furfural process include washing and/or chemical pretreatments prior to fermentation, which increases processing costs. Conversely, residual solids from steam explosion applied in the first stage of the two-stage process, do not require further pretreatment prior to fermentation, in cases where inhibitor resistant yeast strains are used. However, furfural produced from the hemicellulose hydrolysate in the second stage of this process is often recovered and purified using organic solvents that will negatively affect the environment. Therefore, this study compared the technical and economic differences between the one-stage and two-stage methods of co-producing furfural and ethanol from sugarcane lignocelluloses. One-stage furfural production was achieved in the temperature range of 170- 200ºC and acid doses of 0-2 wt.% H2SO4 using sugarcane bagasse, with unwashed solid esidues used for ethanol production. Pretreated lignocelluloses from the two-stage furfural production process were similarly assessed for ethanol production. Mass and energy balances for alternative biorefinery scenarios co-producing furfural and ethanol in the one-stage or two-stage configurations, were obtained with Aspen Plus® V8.8 process simulations, using experimental data either collected in this study or published. The internal rate of return (IRR) of the most promising one-stage furfural and ethanol co-production biorefinery was 12.78%, while the equivalent two-stage biorefinery obtained an IRR of 13.59%. The lowest minimum ethanol selling prices (MESPs) achieved by the one-stage furfural and ethanol co-production biorefineries were 1.14 US$/L and 2.54 US$/L at a desired IRR of 15 and 20%, respectively. The two-stage furfural and ethanol co-production biorefinery achieved economic indicators that were improved by 36-51%, as demonstrated by the lowest MESPs 0.73 US$/L and 1.25 US$/L (at IRRs of 15 and 20%, respectively), in comparison to the one-stage furfural and ethanol co-production biorefinery. One-stage furfural production resulted in significant degradation of cellu-lignin residues, which negatively affected ethanol yield, and the profitability. Improvements in ethanol production due to preservation of cellu-lignin residues in the two-stage furfural production process provided economic benefits. However, the economic potential of furfural and ethanol co-production remained significantly hindered by process energy demands, in the context of energy self-sufficient biorefinery reliant on available feedstock for energy supply. These energy demands decrease the financial viability of furfural production compared to alternative potential co-products.